LEGAL EFFECTS OF RECOGNITION OF SAME-SEX UNIONS: APPLICATION OF EUROPEAN STANDARDS - Novaković, Uroš (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The ECHR requires that persons of the same-sex be in a stable and lasting union in order to determine the existence of family life between them. In order for family life to exist, it is not enough for persons of homosexual orientation to be in a short-term and transient relationship, but a stable union is required, which can be manifested through assumed union, shared place of residence, joint business, acquisition of property in the union. Unlike the previous practice of the ECHR, which until 2010 and the judgment in Schalk and Kopf v. Austria, refused to recognize a relationship between persons of the same sex as a relationship that can be considered in accordance with the rules of family life. considers this relationship as family life, and characterizes the lack of legal regulation and legal protection of these relationships as a violation of the right to respect for family life. Despite the fact that family life is established, the state is not obliged to provide for the conclusion of marriage by a person, but, according to the adoption of the practice of the ECHR, it has an obligation to somehow, i.e. through a certain form, recognize these unions, and in this respect it leaves the home states a wide margin of appreciation. Since the judgment in Schalk and Kopf v. Austria, a relationship between homosexual persons living together indisputably constitutes family life.
Keywords: marriage; same-sex union; family life; registered partnership; European Court of Human Rights